Thermal sensor based zinc oxide diode for low temperature applications - Ocaya, R. O.; Al-Ghamdi, Ahmed; El-Tantawy, F.; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2016)
The device parameters of Al/p-Si/Zn1-xAlxO-NiO/Al Schottky diode for x = 0.005 were investigated over the 50 K-400 K temperature range using direct current-voltage (I-V) and impedance spectroscopy. The films were prepared using the sol gel method followed by spin-coating on p-Si substrate. The ideality factor, barrier height, resistance and capacitance of the diode were found to depend on temperature. The calculated barrier height has a mean. Capacitance-voltage (C-V) measurements show that the capacitance decreases with increasing frequency, suggesting a continuous distribution of interface states over the surveyed 100 kHz to 1 MHz frequency range. The interface state densities, N-SS, of the diode were calculated and found to peak as functions of bias and temperature in two temperature regions of 50 K-300 K and 300 K-400 K. A peak value of approximately 10(12)/eV cm(2) was observed around 0.7 V bias for 350 K and at 3 x 10(12)/eVcm(2) around 2.2 V bias for 300 K. The relaxation time was found to average 4.7 mu s over all the temperatures, but showing its lowest value of 1.58 mu s at 300 K. It is seen that the interface states of the diode is controlled by the temperature. This suggests that Al/p-Si/Zn1-xAlxO-NiO/Al diode can be used as a thermal sensors for low temperature applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Thermal sensor; Low-temperature diode; Heterojunction